More oil, less quality of education? New empirical evidence - Mohammad Reza Farzanegan; Marcel Thum (Technische Universität Dresden, Center of Public and International Economics (CEPIE), 2017)
The resource curse hypothesis suggests that resource-rich countries show lower economic growth rates compared to resource-poor countries. We add to this literature by providing empirical evidence on a new transmission channel of the resource curse, namely, the negative effect of rents on the quality of education. The cross-country analysis for more than 70 countries shows a significantly positive effect of oil rents on the quantity of education measured by government spending on primary and secondary education. Hence, the underspending hypothesis championed by Gylfason (2001) no longer holds with newer data. However, we find a robust and negative effect of oil rents dependency on the current objective and subjective indicators of quality of education, controlling for a set of other drivers of education quality and regional dummies. Despite pending significant shares of GDP on education, oil-rich countries still suffer from an insuficient quality of primary and secondary education,which may hamper their growth potentials. The significant negative effect of oil rents dependency on education quality can be explained by both the demand (e.g., skill acquisition) and supply (e.g., teacher quality) side channels.
urn:nbn:de:bsz:14-qucosa-227300
Keywords: H52; I25; Q32; 330; oil rents; resource curse; quality of education; quantity of education